Peran Kitab Majmu’atul Mahfudzot Dalam Penguasaan Kosakata Bahasa Arab Di MTs Hasan Muchyi Kediri - Azizah, Lutfia Durorul; Hanani, Nurul; Hartanto, Eko Budi (Program Studi Pendidikan Bahasa Arab, 2023)
The research discusses the book Majmu'atul Mahfudzot in Arabic Vocabulary Mastery in Class VIII-A Islamic Junior High School Hasan Muchyi Kediri. The aims of this study were to find out the role of the book Majmu'atul Mahfudzot in mastering Arabic Learning Vocabulary and also to find out the factors that support and inhibit the vocabulary of learning Arabic in class VIII-A Islamic Junior High School Hasan Muchyi Kediri. This study uses a descriptive qualitative method using a type of field research. Data collection techniques using observation, interviews and documentation. The data analysis uses data reduction, data presentation, conclusions. The validity of the data using source triangulation and technique triangulation. Furthermore, the results of the study show that (1) there is a role for the book majmu'atil mahfudzot on Arabic vocabulary mastery in class VIII-A Islamic Junior High School Hasan Muchyi Kediri. (2) the supporting factors are the existence of Mahfudzot lessons using the majmu'atil mahfudzot book, the methods used by the teacher vary, the supporting facilities and infrastructure of the madrasah. The inhibiting factors include the lack of student will, lack of support from parents or friends, dependence on mobile phones.